Colorimetric detection of influenza A (H1N1) virus by a peptide-functionalized polydiacetylene (PEP-PDA) nanosensor. Issue 54 (18th May 2016) - Song, Sinae; Ha, Kab; Guk, Kyeonghye; Hwang, Seul-Gee; Choi, Jong Min; Kang, Taejoon; Bae, Pankee; Jung, Juyeon; Lim, Eun-Kyung
Abstract : ​We developed a peptide-functionalized polydiacetylene nanosensor for pH1N1 virus detection with the naked eye. Abstract : We developed a peptide-functionalized polydiacetylene (PEP-PDA) nanosensor for pandemic H1N1 virus (pH1N1) detection with the naked eye. A PDA nanosensor was fabricated by nano-precipitation and modified with PEP for the specific recognition of pH1N1. The PEP-PDA nanosensor showed unique chromatic properties involving a colour change from blue to red in the presence of pH1N1. We believe that this nanosensor can be applied for the development of a commercially available kit for pH1N1 detection.